The JPS Pathfinding System - Harabor, Daniel; Grastien, Alban (Proceedings of the International Symposium on Combinatorial Search, 2012)
We describe a pathfinding system based on Jump Point Search (JPS): a recent and very successful search strategy that performs symmetry breaking to speed up optimal pathfinding on grid maps. We first modify JPS for grid maps where corner-cutting moves are not allowed. We then describe JPS+: a new derivative search strategy that reformulates an input graph into an equivalent symmetry-reduced form that can be searched more efficiently. JPS and JPS+ were both submitted to the 2012 Grid-based Path Planning Competition.